Pengaruh Intensitas Modal, Intensitas Persediaan, Kebijakan Hutang, Dan Perataan Laba Terhadap Agresivitas Pajak - Murni Ria Lestari; Adhitya Putri Pratiwi (CV. ITTC INDONESIA, 2024)
This research aims to analyze the influence of capital intensity, inventory intensity, debt policy and income smoothing on tax aggressiveness. This research also uses a sample of Non-Primary Consumer Goods Manufacturing Companies (consumer cyclicals) listed on the Indonesian Stock Exchange for the 2018-2022 period. The data used in this research is secondary data in this research in the form of financial reports and annual reports. The sample technique uses the Purposive Sampling Technique, where from 151 Non-Primary Consumer Goods Manufacturing Companies (consumer cyclicals) a sample of 15 companies was obtained for 5 years so that 75 sample data were obtained. The analysis used is Panel Data Regression Analysis using Common Effect Model (CEM) Regression and the data is processed using Eviews Software version 12. The results obtained show the Feasibility Test (f test) Capital Intensity (X1), Inventory Intensity (X2), Policy Debt (X3) and Income Smoothing (X4) had significant effect on Tax Aggressiveness (Y). The results obtained showed using the Partial Test (t test) that only the Inventory Intensity (X2), Debt Policy (X4) variables had significant effect on the Tax Aggressiveness variable (Y), while for the Capital Intensity (X1), Profit Smoothing (X4) variables did not have any significant effect on the Tax Aggressiveness variable (Y).